2018
DOI: 10.1097/md.0000000000013067
|View full text |Cite
|
Sign up to set email alerts
|

Banxia Baizhu Tianma decoction for hyperlipidemia

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The Banxia Baizhu Tianma decoction is made up of six Chinese herbal medicines, including Banxia. Research on rats has shown that the Banxia Baizhu Tianma decoction can reduce serum TC, TG, low-density lipoprotein cholesterol, apolipoprotein B, superoxide dismutase, and malondialdehyde in rats with hyperlipidemia [29]. Moreover, Jiang et al found that the Banxia Baizhu Tianma decoction has a significant effect on body weight and TC in mice with obesity-related hypertension, reducing lipid deposition in the roots of arteries, protecting endothelial cells, reducing apoptosis, decreasing the migration rate caused by oxidized low-density lipoproteins, and maintaining cell morphology [30].…”
Section: Discussionmentioning
confidence: 99%
“…The Banxia Baizhu Tianma decoction is made up of six Chinese herbal medicines, including Banxia. Research on rats has shown that the Banxia Baizhu Tianma decoction can reduce serum TC, TG, low-density lipoprotein cholesterol, apolipoprotein B, superoxide dismutase, and malondialdehyde in rats with hyperlipidemia [29]. Moreover, Jiang et al found that the Banxia Baizhu Tianma decoction has a significant effect on body weight and TC in mice with obesity-related hypertension, reducing lipid deposition in the roots of arteries, protecting endothelial cells, reducing apoptosis, decreasing the migration rate caused by oxidized low-density lipoproteins, and maintaining cell morphology [30].…”
Section: Discussionmentioning
confidence: 99%